Biological reduction of iron to the elemental state from ochre deposits of Skelton Beck in Northeast England - Rahman, Pattanathu K. S. M.; Bastola, Suvechhya (Frontiers in Environmental Science, 2014)
Ochre, consequence of acid mine drainage, is iron oxides-rich soil pigments that can be found in the water drainage from historic base metal and coal mines. The anaerobic strains of Geobacter sulfurreducens and Shewanella denitrificans were used for the microbial reduction of iron from samples of ochre collected from Skelton Beck (Saltburn Orange River, NZ 66738 21588) in Northeast England. The aim of the research was to determine the ability of the two anaerobic bacteria to reduce the iron present in ochre and to determine the rate of the reduction process. The physico-chemical changes in the ochre sample after the microbial reduction process were observed by the production of zero-valent iron which was later confirmed by the detection of elemental Fe in XRD spectrum. The XRF results revealed that 69.16% and 84.82% of iron oxide can be reduced using G. sulfurreducens and S. denitrificans respectively after 8 days of incubation. These results could provide the basis for the development of a biohydrometallurgical process for the production of elemental iron from ochre sediments.